A modified Matrices Approach in Advanced Encryption Standard Algorithm - Abdul Monem Rahma; Atheer Abbas (Engineering and Technology Journal, 2019)
The cryptographic algorithms became the main proceeding for protection of very important data from unauthorized access. There are several cryptographic algorithms to ensure the data, but algorithms must be selected according to speed, strength and the implementation. Thus, choosing the advance encryption standard (AES) for encryption and decryption data because its speed and strength of encryption, flexible, complex processing and its resistance to Brute-force attack. This paper presents enhancement of the AES algorithm to increase the security of the encrypted documents by using different sizes data matrices based on multiple irreducible polynomials with order 2, 4, and 8. The proposed modifications results tested and provide a high randomness.